Clinical, Cytogenetic, and Molecular Findings in Two Cases of Variant t(8;21) Acute Myeloid Leukemia (AML) - Wilde, Lindsay; Cooper, Jillian; Wang, Zi-Xuan; Liu, Jinglan (Frontiers in Oncology, 2019)
t(8;21)(q22;q22) is present in approximately 5-10% of patients with de novo acute myeloid leukemia (AML) and is associated with a better overall prognosis. Variants of the t(8;21) have been described in the literature, however, their clinical and prognostic significance has not been well characterized. Molecular profiling of these cases has not previously been reported but may be useful in better defining the prognosis of this subset of patients. We present two cases of variant t(8;21) AML including clinical, cytogenetic, and molecular data.